Outcomes evaluation of Tshepo programme in promoting socio-economic development among unemployed youth in Tshwane, Gauteng Province - Maimela, Whitney Ngwanakgopa (My University, 2021)
South Africa suffers a high rate of youth unemployment. In the first quarter of 2020, unemployment stood at 63.3 which is an increase from the 55.97% rate in 2019. One of the causes of the high unemployment rate in the country is because employers seek and employ skilled individuals, whilst those without appropriate skills are regarded to be risky investment. Unemployment has a negative impact on the lives of youth and can lead to an involvement in illegal activities due to boredom or desperation to earn some income. The government has initiated several programmes aimed at alleviating youth unemployment and improving the lives of the citizens. One such initiative is the Tshepo programme. The aim of the study was to explore whether and describe how the Tshepo programme is promoting the socio-economic development of the unemployed youth in Tshwane in the Gauteng province of South Africa. The study used a qualitative approach and followed the exploratory case study design. Non-probability purposive sampling was used to select eight (8) participants who met the specified selection criteria. Semi structured interviews were conducted using a semi structured interview schedule to collect data. Subsequently, the data was thematically analysed. As anticipated, the study revealed that the Tshepo programme has somewhat achieved its outcomes of empowering the youth, alleviating poverty, and reducing the unemployment rate amongst youth in the Tshwane area. The findings may contribute knowledge to social work practice regarding how to enhance programme design aimed at empowering unemployed youth. Additionally, the findings may be used as reference during the next National Youth Policy review process
A report on a research study presented to The Department of Social Work, School of Human and Community Development, Faculty of Humanities, University of the Witwatersrand in partial fulfilment of the requirements for the degree of Master of Arts in Social Work, 2021